PENGEMBANGAN MEDIA KOMIKANIK MATERI PESAN DAN INFORMASI TEKS NARASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 4 SDN GEDANGSEWU 1 - Dahniar Widya Kharisma; Mumun Nurmilawati; Poppy Rahmatika Primandiri (Jurnal Manajemen Pendidikan, 2026)
The purpose of this research and development is to determine the validity, practicality, and effectiveness of the Komikanik media (Electronic Cartoon Comics) Message Material and Narrative Text Information for Grade IV Elementary School Students. The development model used in this research is the development studies type with the Formative Tessmer test. The subjects of this research were grade IV students of SDN Gedangsewu 1, totaling 26 students. The data analysis techniques used were qualitative descriptive analysis and quantitative descriptive analysis. Data collection instruments included observation sheets, interview sheets, expert validation sheets, and pretests and posttests. The results of this research show that. (1) The validity score obtained from media experts was 84% ​​and the validity score from material experts was 80% with a very valid category. (2) The results of the practicality test obtained a teacher response score of 92% and an average response score of 26 students in the Field test was 91.5% with a very practical category. (3) The results of the effectiveness test, from the pretest score 42% of students achieved completeness. Then, the posttest results showed that 92% of students achieved mastery. This increase indicates the effectiveness of learning using Komikanik Media (Electronic Cartoon Comics). It can be concluded that the development of Komikanik Media (Electronic Cartoon Comics) is declared very valid, very practical, and effective for use in teaching narrative text messages and information for fourth-grade elementary school students.